FATTY ACID ETHYL ESTERS FROM MICROALGAE OF Scenedesmus ecornis BY ENZYMATIC AND ACID CATALYSIS - Almeida, Gabryelle; Araújo, Pedro; Florentino, Alexandro; Bezerra, Roberto; Carvalho, José; Faustino, Silvia; Ferreira, Irlon (Química Nova, 2018)
Microalgae are an indispensable food source for the various growth stages of mollusks, crustaceans, and several fish species. Using a microalgae biomass present in the Amazonian ecosystem (Macapá-AP), we study extraction methods for fatty acid such as solvent extraction (magnetic stirring and/or Soxhlet) and/or hydrolysis (acid and/or enzymatic catalysis) followed by esterification and/or direct transesterification. Extraction of crude triacylglycerides by mechanical stirring at room temperature was more efficient than continuous reflux (Soxhlet). Subsequently, the lipid extract was subject to transesterification with ethanol and CAL-B as a biocatalyst, leading to production of fatty acid ethyl esters (FAEE). Additionally, FAEEs were prepared by hydrolysis of crude triacylglycerides followed by acid-mediated esterification or enzymatic catalysis (lipase). In this case, the type of catalyst did not significantly influence FAEE yields. In the lipid extract, we identified palmitic, linoleic, oleic, and stearic acids with palmitic acid being the most abundant. Our results suggest that enzymatic catalysis is a viable method for the extraction of lipids in the microalga, Scenedesmus ecornis.